Analisis Kesesuaian dan Daya Dukung Ekowisata Bahari Pulau Mansinam Kabupaten Manokwari - Muhammad Arsyad; Vera Sabariah; Roni Bawole; Nurhani Widiastuti (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Mansinam isle has a potential natural resources with terrestrial and aquatic ecosystems, with varieties of flora, fauna, and outstanding natural beauty. Some of them had not been used optimally, therefore useful programs are required to develop and utilize these resources but still acknowledging the effort of conservation and rehabilitation thus the resources remain sustainable and to improve local community life. The purposes of this research are to assess: 1) the suitability of tourism, 2) ecological carrying capacity, and 3) the hospitality for travelling visitors. A survey method with direct observation technique applied on coral reefs, seagrass beds and coastal ecosystems. The results shows that ecotourism in Mansinam isle as follows: tourism suitability for diving category on ​​coral reef ecosystems at 3 meters depth was very suitable (IKW 82.19 to 89.04) and 10 meters depth is suitable (IKW 76.71). Tourism suitability for snorkeling category on coral reef ecosystems at 3 meters depth is very suitable (IKW 90.12 to 91.36), and seagrass ecosystems is suitable (IKW 78.79). Tourism suitability for beach category is very suitable (IKW 89.29 to 96.43), coastal category is moderately (IKW 70.51 to 76.92). Analysis on supporting capacity and ecological carrying capacity for diving category on coral reef ecosystems is 44 visitors per day, snorkeling 24 visitors per day, seagrass20 visitors per day, beach recreation 18 visitors per day, sun bathing 10 visitors per day, swimming 16 visitors per day, sports tourism 8 visitors per day, and camping tours197 visitors per day. Results shown for esthetics and hospitality values suggested that 52% of respondents stated that Mansinam Island were quite beautiful and 41% said very beautiful, moreover 66% of respondents expressed quite comfortable and 21% said comfortable.